2015
DOI: 10.1017/s0958344015000142
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effectiveness of EFL students’ use of dictionaries and an online corpus for the enhancement of revision skills

Abstract: Qualitative research focusing primarily on advanced-proficiency second language (L2) learners suggests that online corpora can function as useful reference tools for language learners, especially when addressing phraseological issues. However, the feasibility and effectiveness of online corpus consultation for learners at a basic level of L2 proficiency have been relatively unexplored. The current study of Japanese-L1 (first language) learners in an EFL (English as a foreign language) context (N = 117) address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…Their finding shows that the integration of interactive multimedia sources can serve as a special guide to ensure the student achievement in essay writing is outstanding. It is undeniable by Mueller and Jacobsen (2016) including the significant findings from the research that an integrated online collaborative approach is strongly recommended. Supporting research by Iqbal and Muhammad (2015) has shown that multi-sensory that based on interactive multimedia stimulates many senses of the learners.…”
Section: Discussionmentioning
confidence: 99%
“…Their finding shows that the integration of interactive multimedia sources can serve as a special guide to ensure the student achievement in essay writing is outstanding. It is undeniable by Mueller and Jacobsen (2016) including the significant findings from the research that an integrated online collaborative approach is strongly recommended. Supporting research by Iqbal and Muhammad (2015) has shown that multi-sensory that based on interactive multimedia stimulates many senses of the learners.…”
Section: Discussionmentioning
confidence: 99%
“…In 12 of the studies, the exposure to DDL was more than 5 weeks. It seems that studies by Chang [26] and Muller & Jacobsen [33] lasted for the longest time, which was 22 weeks and 6 months respectively. The studies based on longer-time experiment usually started with a course or project and then presented the research questions to evaluate some aspects of DDL, while the shorter-time study often began with the research question and then create an experimental situation mainly in the form of one-time tests or questionnaires.…”
Section: Research Samples and Designsmentioning
confidence: 96%
“…In these studies, the duration of experiment is reported in different ways, which makes the comparison difficult. Most studies introduced it by giving weeks but the second experiment in Muller & Jacobsen [33] is reported by showing months. Besides that, there were two studies [30] [34] describing the duration of DDL by showing semester.…”
Section: Research Samples and Designsmentioning
confidence: 99%
See 2 more Smart Citations